ALGORITHMIZATION OF CONTENT PREPARATION FOR A COMPILATION DISCIPLINE USING ARTIFICIAL INTELLIGENCE TOOLS - Momot, Volodymyr; Lytvynenko, Olena (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
Based on the experience of developing the content of the compilation discipline «Technologies of Training Delivery» at the Alfred Nobel University using the main modern AI tools (ChatGPT 4.0, Gemini and Claude), a robust algorithm is proposed. The main problems that arise when using AI tools, such as initial bias and low trust level among the teaching staff. The possibilities of joint use of AI visualization tools (DAL-E 3.0 neural network) and presentation tools commonly used in the educational process (PowerPoint and Keynote) are shown. The problems of trust that arise during the deep implementation of AI tools in the educational process are considered. Recommendations are given on the systematic use of AI tools in the preparation and improvement of educational content.